From the delivered to the dispatched: masculinity in modern American fiction (1969-1977) - Stilley, Harriet Poppy (The University of Edinburgh, 2017)
There has long been a critical consensus that the presiding mood of America in the late sixties and early seventies was one of pervasive social upheaval, with perpetual ‘crisis’ seeming in many ways the narrative rule. Contemporaneous critics such as Erich Fromm, David Riesman, and William Whyte, together with late-twentieth century writers, Michael Kimmel, Sally Robinson, and David Savran, congruently agree that the post-war American epoch connoted one of expeditious adjustment for white, middle-class men in particular. The specific aim of this thesis is, thus, to elucidate the ways in which the literary fiction of this period by authors John Cheever, James Dickey, Toni Morrison, Cormac McCarthy, and new journalist, Michael Herr, reflects a significantly increased concern for such alterations in the values and attitudes of contemporary cultural life through representations of modern American masculinities. Multiple liberation struggles, including Civil Rights, Feminism, and sexual politics, converged with core economic shifts that transformed the US from an industrial based to a consumerist model. For hegemonic masculinity, this is a transferal from ‘masculine’ industrial labour and the physically expressive body to ‘feminine’ consumerism. This study will first of all underline the extent to which fiction in this period registers those changes through the lens of a fraying of what was once a fortified fabric from which white, patriarchal power was normatively fashioned. What is most disrupted by the paradigm shifts of the era will appear, then, to be a monolithic, coherently bounded American masculinity. However, by way of an interrelated interpretation of contemporaneous feminist and Marxist theory, my research will subsequently show that, rather than being negated, the fabric of that dominant masculinity regenerated and reasserted itself, primarily through the fraught revival of a violent and mythologized hypermasculinity in mainstream US culture. Whether it is through the suburban maladjustment of Eliot Nailles and Paul Hammer, the fraudulent frontier ethic of Ed Gentry and Lewis Medlock, or the more perverse pugnacity of Lester Ballard and internalised racism of Cholly Breedlove, this thesis argues that, by the mid-seventies, numerous American novelists had sought to artistically magnify the ways in which fundamental changes in the patterns of national life were occurring – changes which are represented more often than not as damaging to the normative model of masculinity and the experiential consciousness of men.
Keywords: 1970s; masculinity; American fiction